Genome-wide identification and expression analysis of the ZF-HD gene family in pea (Pisum sativum L.) - Shi, Bowen; Haq, Inzamam Ul; Fiaz, Sajid; Alharthi, Badr; Xu, Ming-Long; Wang, Jian-Lin; Hou, Wei-Hai; Feng, Xi-Bo (Frontiers in Genetics, 2023)
Pea is a conventional grain-feed-grass crop in Tibet and the only high-protein legume in the region; therefore, it plays an important role in Tibetan food and grass security. Zinc finger-homeodomain (ZF-HD) belongs to a family of homozygous heterotypic cassette genes, which play an important role in plant growth, development, and response to adversity stress. Using a bioinformatics approach, 18 PsZF-HD family members were identified. These genes were distributed across seven chromosomes and two scaffold fragments, and evolutionary analysis classified them into two subgroups, MIF and ZHD. The MIF subgroup was subdivided into three subclasses (PsMIFⅠ–III), and the ZHD subgroup was subdivided into five subclasses (ZHDⅠ–V). The PsZF-HD members were named PsMIF1–PsMIF4 and PsZHD1–PsZHD14. Twelve conserved motifs and four conserved domains were identified from PsZF-HD family, of which MIF subgroup only contained one domain, while ZHD subgroup contained two types of domains. In addition, there were significant differences in the three-dimensional structures of the protein members of the two subgroups. Most PsZF-HD genes had no introns (13/18), and only five genes had one intron. Forty-five cis-acting elements were predicted and screened, involving four categories: light response, stress, hormone, and growth and development. Transcriptome analysis of different tissues during pea growth and development showed that PsZHD11, 8, 13, 14 and MIF4 were not expressed or were individually expressed in low amounts in the tissues, while the other 13 PsZF-HDs genes were differentially expressed and showed tissue preference, as seen in aboveground reproductive organs, where PsZHD6, 2, 10 and MIF1 (except immature seeds) were highly expressed. In the aerial vegetative organs, PsZHD6, 1, and 10 were significantly overexpressed, while in the underground root system, PsMIF3 was specifically overexpressed. The leaf transcriptome under a low-nitrogen environment showed that the expression levels of 17 PsZF-HDs members were upregulated in shoot organs. The leaf transcriptome analysis under a low-temperature environment showed stress-induced upregulation of PsZHD10 and one genes and down-regulation of PsZHD6 gene. These results laid the foundation for deeper exploration of the functions of the PsZF-HD genes and also improved the reference for molecular breeding for stress resistance in peas.